2022
DOI: 10.1007/s00392-022-02078-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between non-invasively detected liver fibrosis and in-hospital outcomes in patients with acute coronary syndrome undergoing PCI

Abstract: Background Patients with acute coronary syndrome (ACS) undergoing percutaneous coronary intervention (PCI) still experience a high rate of in-hospital complications. Liver fibrosis (LF) is a risk factor for mortality in the general population. We investigated whether the presence of LF detected by the validated fibrosis 4 (FIB-4) score may indicate ACS patients at higher risk of poor outcome. Methods In the prospective ongoing REAl-world observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
1
6
0
1
Order By: Relevance
“…In addition, the increased prevalence of NSTEMI in individuals with hepatic steatosis and STEMI in those with advanced fibrosis appears to be consistent with previous studies 54,55 . A growing body of evidence has shown that gut‐derived lipopolysaccharides found in advanced liver disease 56,57 are also seen in atherosclerotic plaque that may potentially result in plaque vulnerability and plaque rupture 58,59 .…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In addition, the increased prevalence of NSTEMI in individuals with hepatic steatosis and STEMI in those with advanced fibrosis appears to be consistent with previous studies 54,55 . A growing body of evidence has shown that gut‐derived lipopolysaccharides found in advanced liver disease 56,57 are also seen in atherosclerotic plaque that may potentially result in plaque vulnerability and plaque rupture 58,59 .…”
Section: Discussionsupporting
confidence: 87%
“…58,59 One may postulate that the higher metabolic burden of hepatic steatosis is associated with accelerated coronary artery narrowing and its resultant increased NSTEMI risk; however, the lipopolysaccharide hypothesis, associated with advanced liver disease, may further modify vulnerable coronary plaque characteristics and eventual plaque rupture that lead to acute coronary artery occlusion and STEMI risk. 54 Importantly, this association deserves deeper investigations with further mechanistic studies. Similar to most metabolic diseases, clinicians need to be cognizant that the impact of fatty liver on CVD is a continuum that should not be limited to the binary categorization of hepatic steatosis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…First , although patients with known advanced liver disease (cirrhosis) were excluded, an elevated De Ritis ratio still may be a marker of liver disease and fibrosis 30 . Liver fibrosis detected by FIB‐4 score was associated with more severe presentation of acute coronary syndromes and a worse clinical outcome regardless of other clinical or laboratory variables 31 and a higher risk of cardiovascular events including cardiovascular mortality and all‐cause mortality in patients with cardiovascular disease 32 . Second , previous studies, 15,27 and current analysis showed that an elevated De Ritis ratio was associated with a number of cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 99%